Saddam : The secret life - Coughlin, Con (Macmillan, 2002)
Shortly before a carefully orchestrated series of terrorist attacks devastated the eastern seaboard of the United States on the morning of September 11, 2001, Saddam Hussein, the president of Iraq, placed his troops on "Alert G", the hishest state of military readiness Iraqi troops had seen since the 1991 Gulf War. Saddam himself retreated to one of his heavily forthfied bukers in the family fiefdom of Tikrit, in northern Iraq.